Moral Expertise in the Clinic: Lessons Learned from Medicine and Science. Issue 4 (1st August 2016) - McClimans, Leah; Slowther, Anne
Abstract: Philosophers and others have questioned whether or not expertise in morality is possible. This debate is not only theoretical, but also affects the perceived legitimacy of clinical ethicists. One argument against moral expertise is that in a pluralistic society with competing moral theories no one can claim expertise regarding what another ought morally to do. There are simply too many reasonable moral values and intuitions that affect theory choice and its application; expertise is epistemically uniform. In this article, we discuss how similar concerns have recently threatened to undermine expertise in medicine and science. In contrast, we argue that the application of values is needed to exercise medical, scientific, and moral expertise. As long as these values are made explicit, worries about a pretense to authority in the context of a liberal democracy are ill-conceived. In conclusion, we argue for an expertise that is epistemically diverse.